2020
DOI: 10.1158/1078-0432.ccr-19-2700
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL6 as a Prognostic Biomarker and IL6R as a Therapeutic Target in Biliary Tract Cancers

Abstract: Purpose: Biliary tract cancer (BTC) is a heterogeneous group of rare gastrointestinal malignancies with dismal prognosis often associated with inflammation. We assessed the prognostic value of IL6 and YKL-40 compared with CA19-9 before and during palliative chemotherapy. We also investigated in mice whether IL6R inhibition in combination with gemcitabine could prolong chemosensitivity.Experimental Design: A total of 452 Danish participants with advanced (locally advanced and metastatic) BTC were included from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…Among the current treatment regimens, the antiangiogenic bevacizumab may hold promise for the IL6-expressing stress-high tumors, as increased plasma levels of IL6 are indicative of bevacizumab sensitivity in HGSOC (47). Furthermore, antibodies against IL6, TNF, LIF, CXCL12, or their receptors, some of which are already in clinical use to treat inflammatory diseases, have shown initially promising results in preclinical models when combined with platinum chemotherapy (49)(50)(51)(52). In addition, the regulators up-and downstream of IL6, namely, STAT3 and Toll-like receptors, respectively, have been successfully targeted in resistant cancer models (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…Among the current treatment regimens, the antiangiogenic bevacizumab may hold promise for the IL6-expressing stress-high tumors, as increased plasma levels of IL6 are indicative of bevacizumab sensitivity in HGSOC (47). Furthermore, antibodies against IL6, TNF, LIF, CXCL12, or their receptors, some of which are already in clinical use to treat inflammatory diseases, have shown initially promising results in preclinical models when combined with platinum chemotherapy (49)(50)(51)(52). In addition, the regulators up-and downstream of IL6, namely, STAT3 and Toll-like receptors, respectively, have been successfully targeted in resistant cancer models (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…At present, a large number of studies have confirmed that IL6R is related to tumors (15)(16)(17)(18). Studies have even shown that IL6 could be used as a prognostic biomarker for cholangiocarcinoma, and IL6R could be used as a therapeutic target for cholangiocarcinoma (38). However, there are few studies on IL6R in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 Inflammation mediators are the hallmark of several risk factors associated with ICC. 22 We included several inflammation-based scores and analyzed their prognostic efficacy in this large, multicentre cohort study. It was shown that mGPS was identified as the significant prognostic factor for OS and PFS, independent of CA19-9 value and TNM stage.…”
Section: Discussionmentioning
confidence: 99%